2022
DOI: 10.1177/14034948221092577
|View full text |Cite
|
Sign up to set email alerts
|

Oral health promotion and labour market prospects of socially disadvantaged and unemployed people – a randomised controlled trial

Abstract: Background: Previous studies indicate that poor oral health may constitute a barrier for labour market success. This study examines whether an oral health promotion intervention has an effect on economic self-support, and proximity to the labour market, among socially disadvantaged unemployed people. Methods: From April–June 2018, we enrolled 273 vulnerable people on welfare benefits into a randomised controlled trial. Participants were allocated to either control ( n=159), or intervention ( n=114). Interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…given our results are valid, it seems that even though improvement in daily oral health-care is desirable, increasing the use of the dental care system and receiving oral rehabilitation and preventive measures is an obvious place to start. in this regard, it is relevant that a newly published study has found that an oral health motivation intervention in marginalized people not only led to an increase in the use of the dental care system but also had an effect on the proximity to the labor market [21]. to improve oral health-care habits in marginalized people, it has been suggested to improve the awareness and knowledge in the population and implement supportive systems focusing on holistic and flexible care, outreach, interdisciplinary teams, and effective communication [22].…”
Section: Discussionmentioning
confidence: 99%
“…given our results are valid, it seems that even though improvement in daily oral health-care is desirable, increasing the use of the dental care system and receiving oral rehabilitation and preventive measures is an obvious place to start. in this regard, it is relevant that a newly published study has found that an oral health motivation intervention in marginalized people not only led to an increase in the use of the dental care system but also had an effect on the proximity to the labor market [21]. to improve oral health-care habits in marginalized people, it has been suggested to improve the awareness and knowledge in the population and implement supportive systems focusing on holistic and flexible care, outreach, interdisciplinary teams, and effective communication [22].…”
Section: Discussionmentioning
confidence: 99%
“…however, it is important to note that more than 70% of the most vulnerable individuals in our population did not utilize the scheme. this is unfortunate, as their quality of life could be adversely impacted by poor oral health, and improving their access to dental care services could potentially enhance their labor market attachment [39]. *Among the non-applicants, 52 had missing data due to death or emigration and these were excluded from analyses.…”
Section: Discussionmentioning
confidence: 99%